Automotive in South Asia : From Fringe to Global - Saraf, Priyam (World Bank, Washington, DC, 2016)
The automotive sector is one of the most important industries globally and in South Asia, contributing 19 million of direct and indirect jobs in India alone. This case study identifies both reasons for success and limits on the growth of automotive in South Asia, and recommends policies to enhance its growth. The analysis focuses primarily on the experience of India and Pakistan - two of the biggest markets in South Asia - to understand key trends for the region, and compares their performance with China and Vietnam. The study finds large productivity gaps in this sector, with most OEMs having fragmented operations with low capacity utilization, quality levels and investments in skills below international benchmarks. A second—and connected—challenge is moving up the global value chain (GVCs) through greater innovation, investment in R&D and commercialization of new products which remain below global average. The report relies on the latest available data and tools as well as new evidence collected from semi-structured surveys and primary interviews with the senior executives, middle management and plant-level technical staff in a cross-section of automotive firms. The study documents, in particular, experiences of leading auto-parts manufacturers who distinguished themselves by achieving scale and operational excellence by linking to GVCs. What did that require? How did they overcome the fixed cost to exporting? In its final section, the study summarizes policy recommendations to unblock the barriers to achieving higher productivity with job-creation, and move from a ‘domestic growth under protection’ model to a more sustainable ‘productivity driven global growth’ model.